Can Increases in CHIP Copayments Reduce Program Expenditures on Prescription Drugs? - Sen, Bisakha (Centers for Medicare & Medicaid Services, 2014)
OBJECTIVE: The primary aim is to explore whether prescription drug expenditures by enrollees changed in Alabama’s CHIP program, ALL Kids, after copayment increases in fiscal year 2004. The subsidiary aim is to explore whether non-pharmaceutical expenditures also changed. DATA SOURCES: Data on ALL Kids enrollees between 1999–2007, obtained from claims files and the state’s administrative database. STUDY DESIGN: We used data on children who were enrolled between one and three years both before and after the changes to the copayment schedule, and estimate regression models with individual-level fixed effects to control for time-invariant heterogeneity at the child level. This allows an accurate estimate of how program expenditures change for the same individual following copayment changes. Primary outcomes of interest are expenditures for prescription drugs by class and brand-name and generic versions. We estimate models for the likelihood of any use of prescription drugs and expenditure level conditional on use. PRINCIPAL FINDINGS: Following the copayment increase, the probability of any expenditure decline by 5.8%, brand name drugs by 6.9%, generic drugs by 7.4%. Conditional on any use, program expenditures decline by 7.9% for all drugs, by 9.6% for brand name drugs, and 6.2% for generic drugs. The largest declines are for antihistamine drugs; the least declines are for Central Nervous System agents. Declines are smaller and statistically weaker for children with chronic health conditions. Concurrent declines are also seen for non-pharmaceutical medical expenditures. CONCLUSIONS: Copayment increases appear to reduce program expenditures on prescription drugs per enrollee and may be a useful tool for controlling program costs.